PENGARUH IMPULSE PERSONALITY, REFERENCE GROUP, DAN IMPULSE BUYING TENDENCY TERHADAP IMPULSE BUYING BEHAVIOR. (STUDI KASUS PADA CUSTOMER SKINCARE DI DIY) - Salsabila Eka Putri Nur Rahman; Bianka Andriyani; Wing Wahyu Winarno (Jurnal Ekonomi Dan Bisnis, 2026)
The skincare industry in Indonesia has experienced significant growth, Particularly among residents of the Special Region of Yogyakarta (DIY). This trend has led to an increase in Impulse buying behavior among skincare consumers, driven by both internal and external factors. This study aims to examine the influence of Impulse personality, Reference group, and Impulse buying tendency on Impulse buying behavior among skincare customer in DIY, This research employs a quantitative approach with data collection conducted via a questionnaire distributed using Google Forms. The study included 100 respondents who are consumers of skincare products in the Special Region of Yogyakarta. The sampling method used was purposive sampling, with the criterion that respondents had previously purchased skincare products. The data obtained was then analysed using IBM SPSS Statistic 25. The results of this study demonstrate that impulse personality, reference group, and impulse buying tendency have a significant and positive influence on impulse buying behavior (a case study of skincare customers in DIY).